The impact of dietary fibers on Clostridioides difficile infection in a mouse model - Wu, Zhengjie; Xu, Qiaomai; Wang, Qiangqiang; Chen, Yunbo; Lv, Longxian; Zheng, Beiwen; Yan, Ren; Jiang, Huiyong; Shen, Jian; Wang, Shuting; Wang, Kaicen; Xia, Jiafeng; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Diets rich in fiber may provide health benefits and regulate the gut microbiome, which affects the immune system. However, the role of dietary fiber in Clostridioides difficile infection (CDI) is controversial. Here, we investigated the use of fermentable fibers, such as inulin or pectin, to replace the insoluble fiber cellulose to explore how dietary fiber affects C. difficile-induced colitis in mice through intestinal microecology and metabolomics. Using C. difficile VPI 10463, we generated a mouse model of antibiotic-induced CDI. We evaluated disease outcomes and the microbial community among mice fed two fermentable fibers (inulin or pectin) versus the insoluble fiber cellulose. We analyzed and compared the gut microbiota, intestinal epithelium, cytokine levels, immune responses, and metabolites between the groups. Severe histological injury and elevated cytokine levels were observed in colon tissues after infection. Different diets showed different effects, and pectin administration protected intestinal epithelial permeability. Pectin also steadily increased the diversity of the microbiome and decreased the levels of C. difficile-induced markers of inflammation in serum and colonic tissues. The pectin group showed a higher abundance of Lachnospiraceae and a lower abundance of the conditionally pathogenic Enterobacteriaceae than the cellulose group with infection. The concentration of short-chain fatty acids in the cecal contents was also higher in the pectin group than in the cellulose group. Pectin exerted its effects through the aryl hydrocarbon receptor (AhR) pathway, which was confirmed by using the AhR agonist FICZ and the inhibitor CH2223191. Our results show that pectin alters the microbiome and metabolic function and triggers a protective immune response.